Sınıf III ve open-bite bir olgunun cerrahi tedavisi (olgu sunumu) - (:unkn) unknown (My University, 2012)
Amaç: Olgumuzda çiğneme, dudak yetersizliği ve estetik şikayetleri olan hastanın ortognatik tedavisi sunulmaktadır. Materyal-Method: Ortognatik cerrahi sonrası öngörü ve cerrahi aşamasındaki planlamanın ve iskeletsel bozukluğun daha iyi saptanması için hastanın sefalometrik analizi, CT si alınıp bilgisayar ortamına aktarıldı. Şiddetli açık kapanış ve sınıf III anomaliden dolayı kabul edilebilir estetik ve fonksiyonel sonuçlar için ortognatik cerrahi kaçınılmaz olduğu görüldü. Cerrahi aşamasında üst çene 4mm öne ve 4mm gömülüp, 3.5 derece saat yönünde rotasyon, alt çenede ise 9mm geriye 5.5 derece saat yönünün tersi yönünde rotasyon yapıldı. Sonuç: Üst çenenin gömülmesi ile ön yüz yüksekliğinde azalma ve S-Go/N-Me oranında %2 artış sağladı. Açık kapanış ise üst çenenin saat yönünde, alt çeneninde saat yönünün tersi yönünde rotasyon ile düzeltildi. Sınıf I kanin ve molar ilişki, kabul edilebilir overbite, dengeli bir yumuşak doku ilişkisi ve fonksiyon da önemli düzelmeler elde edildi.

Aim: The aim of this case report was to present the orthognathic surgery of a patient whose complaints were difficulty in chewing, lip incompetence and aesthetic problems. Material-Method: To determine the skeletal deformity and successful surgical planning and accurate prediction of orthognathic surgery outcomes, cephalometric analysis and 3-D CT images of the patient were acquired and the data were transferred to the PC. Due to the severity of the skeletal open bite and Class III malocclusion, orthognathic surgery was inevitable to achieve acceptable results in aesthetic and functional aspects. The maxilla LeFort I advancement (4mm), maxillary impaction (4mm) with clockwise rotation of 3.5 degrees and the mandible was moved 9.0 mm backward with a counter clockwise rotation of 5.5 degrees at surgery. Results: Intrusion of the maxilla reduced the facial height and S-Go/N-Me ratio showed an increase of 2. The open bite improved due to clockwise rotation of maxilla and the auto-rotation of the mandible. Class I molar and canine relationship was achieved. The final outcome of the treatment was a substantial improvement in function and aesthetics. The patient’s soft tissue profile became more balanced and Class I molar relationship with an acceptable overbite was achieved.
Surgical treatment of a patient with a class III and open bite: Case report
Keywords: Diş Hekimliği